The Revolution in Text Mining for Historical Analysis is Here. - Guldi, Jo (American Historical Review, 2024)
The article focuses on different approaches to text mining in the field of digital history. The author discusses three trends, including the silences and exclusions of the archive, the study of change over time, and the impulse to theorize the “fit” between particular problems of archives, and explores how they can impact the historical field.